Electrochemistry of Thin Films with In Situ/Operando Grazing Incidence X‐Ray Scattering: Bypassing Electrolyte Scattering for High Fidelity Time Resolved Studies. Issue 42 (21st September 2021) - Paulsen, Bryan D.; Giovannitti, Alexander; Wu, Ruiheng; Strzalka, Joseph; Zhang, Qingteng; Rivnay, Jonathan; Takacs, Christopher J.
Abstract: Electroactive polymer thin films undergo repeated reversible structural change during operation in electrochemical applications. While synchrotron X‐ray scattering is powerful for the characterization of stand‐alone and ex situ organic thin films, in situ/operando structural characterization has been underutilized—in large part due to complications arising from supporting electrolyte scattering. This has greatly hampered the development of application relevant structure property relationships. Therefore, a new methodology for in situ/operando X‐ray characterization that separates the incident and scattered X‐ray beam path from the electrolyte is developed. As a proof of concept, the operando structural characterization of weakly‐scattering, organic mixed conducting thin films in an aqueous electrolyte environment is demonstrated, accessing previously unexplored changes in the π‐π peak and diffuse scatter, while capturing the solvent swollen thin film structure which is inaccessible in previous ex situ studies. These in situ/operando measurements improve the sensitivity to structural changes, capturing minute changes not possible ex situ, and have multimodal potential such as combined Raman measurements that also serve to validate the true in situ/operando conditions of the cell. Finally, new directions enabled by this in situ/operando cell design are examined and state of the art measurements are compared. Abstract : Electrolyte scattering and absorption is an obstinate problem impeding the operando characterization of weakly scattering thin films in electrochemical systems. By separating the contacting electrolyte from the X‐ray path, the frit cell allows high fidelity time resolved operando scattering that heretofore is impossible. These results reveal the inadequacies of ex situ methods and open new possibilities for multi modal characterization.